Analiza tipului de leadership din Primăria municipiului Cluj-Napoca - Alexandra Bianca Andrianu (Revista Transilvană de Ştiinţe Administrative, 2018)
Leadership is one of the main factors that can contribute to the rise or fall of an organization or institution. A leader is the trigger, if I might say, of a chain reaction, based on his/her approach, style of leadership and behavior. The fact that a single person has such impact on motivation, group or individual work is fascinating, especially when that person is actually doing a good job, making his/her followers to reach their highest level of performance. Therefore, this analysis wants to see if the leaders from Cluj-Napoca Municipality have what is needed in order to bring up the best from their personnel.